1991
DOI: 10.1038/bjc.1991.131
|View full text |Cite
|
Sign up to set email alerts
|

Primary systemic therapy for operable breast cancer

Abstract: Summary Eighty-eight patients presenting with operable breast cancer of 4 cm or greater in diameter (T2, T3, NO, NI, MO) have received primary systemic therapy. Response was assessed following 12 weeks of systemic therapy by linear regression analysis of changes in tumour volume. Definitive locoregional surgery (mastectomy n = 82, wide local excision n = 6) was performed on completion of systemic therapy (3-6 months). Response was observed in 24 (39%) of the 61 patients who received endocrine therapy; all 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 16 publications
1
25
0
3
Order By: Relevance
“…In the remaining patients, tumour response was assessed at 12 weeks by regression analysis of the tumour volumes from weeks 4 to 12. Using 95% confidence intervals, those tumours that had a regression line with a significantly negative gradient were classified as responding, whereas those that had a significantly positive gradient were classified as progressing (Anderson et al, 1991;Cheung and Johnson, 1991). Any tumour whose regression line was not significantly deviant from the horizontal was classified as static.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the remaining patients, tumour response was assessed at 12 weeks by regression analysis of the tumour volumes from weeks 4 to 12. Using 95% confidence intervals, those tumours that had a regression line with a significantly negative gradient were classified as responding, whereas those that had a significantly positive gradient were classified as progressing (Anderson et al, 1991;Cheung and Johnson, 1991). Any tumour whose regression line was not significantly deviant from the horizontal was classified as static.…”
Section: Methodsmentioning
confidence: 99%
“…After April 1987, first-line hormone therapy was only offered to women with oestrogen receptor (ER)-moderate/-rich (> 20 fmol mg-1 protein) tumours, and CHOP was reserved for those women whose tumours failed to respond to hormone therapy and for those with ER-negative/-poor tumours. Response data have been published previously (Anderson et al, 1991). After a median follow-up of 7.5 years, there is no difference in survival between those women given initial hormone therapy and those given chemotherapy, with neither group having yet reached its median survival.…”
mentioning
confidence: 89%
“…This has been reported in various studies though % increase may differ. [2,3,4,5,6] . In our study, before giving neoadjuvant chemotherapy only three [12%] patients were found eligible for breast conservation surgery, whereas sixteen [16%] were offered this surgery afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…The complete pathological response rate of 18% in our study occurred following chemotherapy and radiotherapy, but no comparable published data are available. However, a complete pathological response rate of 17% has been obtained in operable tumours following similar chemotherapy (Anderson et al, 1991). In their study, primary systemic therapy was used on a selective basis for patients with operable breast cancer of 4 cm or greater in diameter, i.e.…”
Section: Discussionmentioning
confidence: 99%